Endophytic fungi isolated from Heliotropium indicum and their antagonism activity toward Fusarium solani and F. oxysporum - ALI MUSTOFA; UTAMI SRI HASTUTI; HENDRA SUSANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mustofa A, Hastuti US, Susanto H. 2024. Endophytic fungi isolated from Heliotropium indicum and their antagonism activity toward Fusarium solani and F. oxysporum. Biodiversitas 25: 5063-5073. Endophytic fungi have great potential as biological control agents due to their ability to produce various bioactive compounds that can inhibit the growth of plant pathogens. One genus of pathogens that is often a problem in agriculture is Fusarium, which causes wilt disease in various types of plants. This study aimed to identify endophytic fungi from the leaves and stems of Heliotropium indicum, analyzed the content of secondary metabolites in plant extracts and endophytic fungal isolates, and evaluated the antagonistic potential of endophytic fungal isolates against pathogenic fungi. This study consisted of observing the location of endophytic fungi in plant tissues, identification of endophytic fungi, detection of secondary metabolite in fluid culture of each endophytic fungi and H. indicum, and antagonism test. The histological observations showed that endophytic fungi are found in the leaf epidermal, sponge, and parenchyma tissue. There were ten endophytic fungi isolates found in leaves and stems, namely Nigrospora gorlenkoana, N. guilinensis, N. musae, N. oryzae, N. rubi, Nigrospora sp. 1, Nigrospora sp. 2, Nigrospora sp. 3, Nigrospora sp. 4, and Penicillium oxalicum. The 10 endophytic fungal isolates including leaf and stem extracts of H. indicum contained secondary metabolite compounds; however, the species Nigrospora sp. 2 had high potential metabolite compounds. These metabolite compounds were able to inhibit the mycelial growth of Fusarium oxysporum, indicating their potential as biocontrol agents. The antagonism test results showed that the ten fungi isolates have antagonism effect toward F. solani and F. oxysporum. The highest antagonism effect against F. oxysporum was 77.2%, the lowest antagonism effect was 46.5%, the highest antagonism effect against F. solani was 64%, and the lowest was 28.2%. The antagonism mechanism of micoparasitism can be seen from the microscopic observations.